Revisiting the Immune Balance Theory: A Neurological Insight Into the Epidemic of COVID-19 and Its Alike - Wu, Junjiao; Tang, Yu (Frontiers in Neurology, 2020)
As the pandemic of COVID-19 is raging around the world, the mysteriousness of severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) coronavirus is being revealed by the concerted endeavors of scientists. Although fever and pneumonia are typical symptoms, COVID-19 patients exhibit multiple neurological complications. In this interim review, we will summarize the neurological manifestations and their potential causes in COVID-19. Similar to the other two fatal respiratory coronaviruses, SARS-CoV and Middle East respiratory syndrome coronavirus (MERS-CoV), SARS-CoV-2 also shows to be neuroinvasive that may spread from the periphery to brain, probably by the retrograde axonal transport. The invaded viruses may directly disrupt the complex neural circuits, and raise a chronic activation of immune responses. In another hand, multiple organ failure in severe COVID-19 is caused by the systemic acute immune responses, and unsurprisingly caused the brain inflammation and led to encephalitis. However, in the central nervous system (CNS), the activation of resident immune cells including microglia and astrocytes may lead to chronic immune imbalance, which underlies the potential long-term effects in synaptic changes and neuropsychiatric impairments. The neuroinvasive biology also provides a possible link with the Braak staging of neurodegenerative diseases such as Parkinson’s disease (PD). Although with considerable advances, the neurotropic potential and chronic neurological effects caused by SARS-CoV-2 infections warrant further investigations.